How Do MinC-D Copolymers Act on Z-Ring Localization Regulation? A New Model of Bacillus subtilis Min System - Wang, Na; Zhang, Tingting; Du, Shuheng; Zhou, Yao; Chen, Yaodong (Frontiers in Microbiology, 2022)
Division site selection in rod-shaped bacteria is strictly regulated spatially by the Min system. Although many sophisticated studies, including in vitro recombination, have tried to explain these regulations, the precise mechanisms are still unclear. Previous model suggested that the concentration gradient of MinC, an FtsZ inhibitor, regulates the position of the Z-ring in cell. In Escherichia coli, the oscillation of MinCDE proteins leads to a gradient of Min proteins with the average concentration being lowest in the middle and highest near the poles. In contrast to Min system of E. coli, the Min system of Bacillus subtilis lacks MinE and exhibits a stable concentration distribution, which is regulated by the binding of DivIVA to the negative curvature membrane. The Min proteins first accumulate at the poles of the cell, and re-localize near the division site when the membrane invagination begins. It is inconsistent with the previous model of high concentrations of MinC inhibiting Z-ring formation. Our preliminary data here using electron microscopy and light scattering technology reported that B. subtilis MinC (BsMinC) and MinD (BsMinD) also assembled into large straight copolymers in the presence of ATP, similar to the Min proteins of E. coli. Their assembly is fast and dominated by MinD concentration. When BsMinD is 5 µM, a clear light scattering signal can be observed even at 0.3 µM BsMinC. Here, we propose a new model based on the MinC-D copolymers. In our hypothesis, it is not the concentration gradient of MinC, but the MinC-D copolymer assembled in the region of high concentration MinD that plays a key role in the regulation of Z-ring positioning. In B. subtilis, the regions with high MinD concentration are initially at both ends of the cell, and then appear at midcell when cell division began. MinC-D copolymer will polymerize and form a complex with MinJ and DivIVA. These complex capture FtsZ protofilaments to prevent their diffusion away from the midcell and narrow the Z-ring in the middle of the cell.